Metabolic interaction between amino acid deprivation and cisplatin synergistically reduces phosphoribosyl-pyrophosphate and augments cisplatin cytotoxicity - Wahwah, Nisreen (Sci Rep, 2020)
Cisplatin is a mainstay of cancer chemotherapy. It forms DNA adducts, thereby activating poly(ADP-ribose) polymerases (PARPs) to initiate DNA repair. The PARP substrate NAD(+) is synthesized from 5-phosphoribose-1-pyrophosphate (PRPP), and we found that treating cells for 6 h with cisplatin reduced intracellular PRPP availability. The decrease in PRPP was likely from (1) increased PRPP consumption, because cisplatin increased protein PARylation and PARP1 shRNA knock-down returned PRPP towards normal, and (2) decreased intracellular phosphate, which down-regulated PRPP synthetase activity. Depriving cells of a single essential amino acid decreased PRPP synthetase activity with a half-life of ~ 8 h, and combining cisplatin and amino acid deprivation synergistically reduced intracellular PRPP. PRPP is a rate-limiting substrate for purine nucleotide synthesis, and cisplatin inhibited de novo purine synthesis and DNA synthesis, with amino acid deprivation augmenting cisplatin’s effects. Amino acid deprivation enhanced cisplatin’s cytotoxicity, increasing cellular apoptosis and DNA strand breaks in vitro, and intermittent deprivation of lysine combined with a sub-therapeutic dose of cisplatin inhibited growth of ectopic hepatomas in mice. Augmentation of cisplatin’s biochemical and cytotoxic effects by amino acid deprivation suggest that intermittent deprivation of an essential amino acid could allow dose reduction of cisplatin; this could reduce the drug’s side effects, and allow its use in cisplatin-resistant tumors.